2018
DOI: 10.1016/j.puhe.2018.01.027
|View full text |Cite
|
Sign up to set email alerts
|

The association of fruit and vegetable consumption with changes in weight and body mass index in Chinese adults: a cohort study

Abstract: Increase in FV consumption was associated with statistically significant weight loss and decrease in BMI among Chinese men, and, although suggested, weight loss among women was not significant. Considering the protective effect of FV on human health, increasing FV consumption in the Chinese population is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
2
22
0
1
Order By: Relevance
“…Among women with a body mass index (BMI) <23 kg/m 2 increased fruit intake was associated with a 13% lower risk of becoming overweight or obese in older age ( p = 0.01). A 2018 cohort study (4357 middle age participants; 5 years) observed that increased fruit and vegetable intake was associated with a significant decrease in body weight and BMI among Chinese men and similar but not significant change in body weight and BMI among women [99]. A large-scale Canadian population-based survey (26,340 individuals) observed that compared to individuals with <1 fruit serving/day those with >2 fruit servings/day had a 10% lower risk for obesity and 12% lower risk of abdominal obesity (all p for trend <0.05) [100].…”
Section: Emerging Health Benefits Associated With Whole Fruits Andmentioning
confidence: 99%
“…Among women with a body mass index (BMI) <23 kg/m 2 increased fruit intake was associated with a 13% lower risk of becoming overweight or obese in older age ( p = 0.01). A 2018 cohort study (4357 middle age participants; 5 years) observed that increased fruit and vegetable intake was associated with a significant decrease in body weight and BMI among Chinese men and similar but not significant change in body weight and BMI among women [99]. A large-scale Canadian population-based survey (26,340 individuals) observed that compared to individuals with <1 fruit serving/day those with >2 fruit servings/day had a 10% lower risk for obesity and 12% lower risk of abdominal obesity (all p for trend <0.05) [100].…”
Section: Emerging Health Benefits Associated With Whole Fruits Andmentioning
confidence: 99%
“…The Chinese Health and Nutrition study (2387 women; mean baseline age 46 years and BMI of 23.3) observed in middle-aged normal-weight women that each 100 g/day increase in total FV reduced weight by −0.14 kg and BMI by −0.29 over six years. Still, these reductions did not achieve statistical significance [ 33 ]. Despite the study’s finding of an insignificant association with weight loss, the Chinese still recommended an increased FV intake to their population to help protect against long-term risk of weight gain.…”
Section: Observational Studiesmentioning
confidence: 99%
“…HPV genotyping by HybriMax was performed using residual Pap test specimens with the HPV GenoArray Test Kit (HybriBio Ltd), and cases were divided into the high-risk HPV infection group and "others" (including low-risk HPV and negative cases). This assay can identify 21 types of HPV, including 15 high-risk types (16,18,31,33,35,39,45,51,52,53,56,58,59, 66, and 68). The low-risk HPV types include types 6,11,42,43,44, and CP8304, which were identi ed using the ow-through hybridization technique performed with a TC-96/G/H6 HPV DNA Ampli cation Analyzer and an HMM-2 fast nucleic acid molecule hybridization instrument (HybriBio Ltd).…”
Section: Clinical Laboratory Testsmentioning
confidence: 99%